Biology science practicum learning: An evaluation study in junior high school of Ngemplak-Indonesia - Try Ramadhan; Slamet Suyanto (JPBI (Jurnal Pendidikan Biologi Indonesia), 2020)
Practical activities are the main activities of learning biology whose implementation is rarely evaluated. This study aimed to determine the quality of biology practicum which includes planning and implementation of biology practicum and student learning outcomes thereafter. The population in this study was students, teachers and and laboratory assistant in Junior High School (JHS) 2 Ngemplak, Indonesia. Purposive sampling was used as sampling technique, in which the sample were 93 students of class VIII A to VIII C, 1 teachers and 1 laboratory assistant. The instruments used in this study were observation sheets. The evaluation criteria were adjusted based on the Regulation of the Minister of National Education. Data were analyzed descriptively and qualitatively. The results inform that the planning and implementation of biology practicum activities were in good categories. In addition, student learning outcomes have also exceeded the minimum completeness score. The results of this study indicate the importance of practicum activities and their contribution to biology learning outcomes. Therefore, the implementation of practicum is highly recommended to be optimized in other schools.Biology science practicum learning: An evaluation study in junior high school of Ngemplak-Indonesia